Long-term Effects of India's Childhood Immunization Program on Earnings and Consumption Expenditure: Comment - David Roodman (Institute for Replication (I4R), 2024)
Summan, Nandi, and Bloom (2023; SNB) finds that exposure of babies to India's Universal Immunization Programme (UIP) in the late 1980s increased their weekly wages in early adulthood by 0.138 log points and per-capita household consumption 0.028 points. But the results are attained by regressing on age, in years, while con-trolling for year of birth-two variables that, as constructed, are nearly collinear. The results are therefore attributable to trends during the one-year survey period, such as inflation. A randomization exercise shows that when the true impacts are zero, the SNB estimator averages 0.088 points for wages and 0.039 points for consumption.
Keywords: 330